2015
DOI: 10.1037/xlm0000058
|View full text |Cite
|
Sign up to set email alerts
|

Modality specificity and integration in working memory: Insights from visuospatial bootstrapping.

Abstract: The question of how meaningful associations between verbal and spatial information might be utilized to facilitate working memory performance is potentially highly instructive for models of memory function. The present study explored how separable processing capacities within specialized domains might each contribute to this, by examining the disruptive impacts of simple verbal and spatial concurrent tasks on young adults' recall of visually presented digit sequences encountered either in a single location or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 72 publications
(149 reference statements)
4
48
0
Order By: Relevance
“…These findings suggest that memory for instructions, including binding movements with objects, at least partly relies on visuospatial WM, perhaps through orienting attention to objects while building a sequential representation of spatially coded movements. This is consistent with the finding of a previous study that visuospatial WM capacity predicted the learning of new motor sequences (Bo & Seidler, 2009), and is also in line with the suggestion that successful verbal-visuospatial binding within the episodic buffer draws on spatial working memory resources (Allen, Havelka, Falcon, Evans, & Darling, 2015). 25 Running head: Working memory in spoken instructions Across all three experiments, a reliable enactment benefit emerged, consistent with research in children (Gathercole et al, 2008) and using written instruction with young adults (Koriat, Ben-Zur, & Nussbaum, 1990;Yang et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…These findings suggest that memory for instructions, including binding movements with objects, at least partly relies on visuospatial WM, perhaps through orienting attention to objects while building a sequential representation of spatially coded movements. This is consistent with the finding of a previous study that visuospatial WM capacity predicted the learning of new motor sequences (Bo & Seidler, 2009), and is also in line with the suggestion that successful verbal-visuospatial binding within the episodic buffer draws on spatial working memory resources (Allen, Havelka, Falcon, Evans, & Darling, 2015). 25 Running head: Working memory in spoken instructions Across all three experiments, a reliable enactment benefit emerged, consistent with research in children (Gathercole et al, 2008) and using written instruction with young adults (Koriat, Ben-Zur, & Nussbaum, 1990;Yang et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…These finding do not seem compatible with our original predictions. Allen et al (2015) provided evidence that meaningful multimodal coding may involve processes occurring at the encoding phase (see also Riby and Orme, 2013). This perhaps leaves the same processes to be employed in retrieval of the two stimulus sets and a richer memory representation being more readily available for the high semantic stimuli (indexed by behavioral performance).…”
Section: Discussionmentioning
confidence: 96%
“…In a similar context, Allen and colleagues investigated the beneficial effect of meaningful spatial layouts (a well-known keypad) for verbal working memory performance (Allen et al, 2015; see also, Darling and Havelka, 2010; Darling et al, 2012). Allen et al showed that spatial interference during the encoding phase, but not the recall phase, removed the positive effect of spatial semantics.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental stimuli and procedure were modeled on the studies of (Allen et al, In press; Darling et al, 2012, 2014; Darling and Havelka, 2010). Sequences of six digits were created in which the digits 0–9 were randomly sampled without replacement.…”
Section: Experiments 2: Visuospatial Bootstrapping Effectmentioning
confidence: 99%
“…Specifically, when subjects are presented with sequences of digits in a spatial array, immediate verbal recall of these digits (akin to a digit span test) improves when digits are presented in a familiar visuospatial context (a typical keypad display) compared to an unfamiliar visuospatial context (an atypical keypad display; Allen et al, In press; Darling et al, 2012, 2014; Darling and Havelka, 2010). This ‘visuospatial bootstrapping effect’ is thought to reflect facilitated recall when verbal digit information can be linked to pre-existing visuospatial representations.…”
Section: Introductionmentioning
confidence: 99%